Isolation and Identification of Phenolic Compounds in Guava Leaves and Assessment of their Cytotoxic Effects Against AMJ-13 and MCF-7 Breast Cancer Cell Lines - Kadhim, Enas J.; Kareem, Ashwaq T. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Psidium guajava, commonly known as guava, is a tropical tree prized for its nutritious fruit and medicinal properties. This member of the Myrtacease family is rich in phytochemicals, which are natural compounds with potential health benefits. Studies have shown that guava leaves and fruits possess various pharmacological activities, including anti-cancer properties against several cancer cell lines. Objectives: This study aimed to isolate and identify phenolic compounds in guava leaves and assess their cytotoxic activity against AMJ-13 and MCF-7 cell lines by ethyl acetate fraction of guava leaves grown in Iraq. Methods: The researchers will employ High-performance liquid chromatography (HPLC) and Fourier transform infrared (FTIR) techniques to analyze the guava leaf extract. Subsequently, preparative High-performance liquid chromatography was used to isolate the specific phenolic compounds of interest, and a colorimetric MTT reduction assay, was conducted using guava extract to assess their effects on human cancer cell lines. Results: The researchers successfully isolated pure samples of caffeic acid, luteolin, and Gallic acid, which are all flavonoids, from the guava leaf extract using preparative High-performance liquid chromatography. These isolated phenolic compounds were from ethyl acetate fraction (F3). This enriched fraction was tested for its cytotoxic activity against the Iraqi AMJ-13 and human MCF7 breast cancer cell lines. The results showed a decrease in cell viability, indicating the fraction’s potential anti-cancer properties. The fraction was more effective against the Iraqi AMJ-13 cells with an IC50 value of 414.3 μg /ml, compared to the human MCF7 cells with an IC50 value of 698.3 μg /ml. Conclusion: The analytical techniques used in this study, like HPLC and FTIR, provided a detailed profile of the phenolic compounds present in guava leaves. This information, combined with the cytotoxic tests, suggests that guava leaves have the potential to kill cancer cells in a concentration-dependent manner.